2014
DOI: 10.1037/a0037204
|View full text |Cite
|
Sign up to set email alerts
|

Encoding and retrieval processes involved in the access of source information in the absence of item memory.

Abstract: The current study sought to examine the relative contributions of encoding and retrieval processes in accessing contextual information in the absence of item memory using an extralist cuing procedure in which the retrieval cues used to query memory for contextual information were related to the target item but never actually studied. In Experiments 1 and 2, participants studied 1 category member (e.g., onion) from a variety of different categories and at test were presented with an unstudied category label (e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 60 publications
3
26
1
Order By: Relevance
“…The result that source identification of unrecalled targets was no different for related versus unrelated pairs is contrary to Ball et al (2014Ball et al ( , p. 1282 who suggested that in the related pairs the cue and target would share features and the cue word would thus be better able to access context generated by the target word which, in turn, would be associated with location information regarding the target word. This can be seen in Fig.…”
Section: Effects Of Type Of Pair On Source Identificationcontrasting
confidence: 80%
See 3 more Smart Citations
“…The result that source identification of unrecalled targets was no different for related versus unrelated pairs is contrary to Ball et al (2014Ball et al ( , p. 1282 who suggested that in the related pairs the cue and target would share features and the cue word would thus be better able to access context generated by the target word which, in turn, would be associated with location information regarding the target word. This can be seen in Fig.…”
Section: Effects Of Type Of Pair On Source Identificationcontrasting
confidence: 80%
“…Two other effects from previous research literature were replicated. Source identification of unrecalled target words was above chance level, as reported in previous research literature (Ball et al, 2014;Cook et al, 2006). Also, source identification performance for cues and targets was positively correlated as indicated by the values of the phi correlations.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…This finding, of course, does not demonstrate source memory for unrecalled targets, as remembering the source of the cue would be sufficient for a correct source judgment. Furthermore, even without cue-context binding, a semantically related but non-studied cue was shown to elicit correct source discrimination after failed target recall, as long as the cue could reinstate the encoding context (Ball, DeWitt, Knight, & Hicks 2014). A similar argument applies to a study by Kurilla and Westerman (2010) who used word-fragment completion followed by an old/new judgment and a source judgment after an OLD response.…”
mentioning
confidence: 78%